Eco-social processes influencing infectious disease emergence and spread. Issue 1 (9th September 2016) - JONES, BRYONY A.; BETSON, MARTHA; PFEIFFER, DIRK U.
SUMMARY: The complexity and connectedness of eco-social processes have major influence on the emergence and spread of infectious diseases amongst humans and animals. The disciplinary nature of most research activity has made it difficult to improve our understanding of interactions and feedback loops within the relevant systems. Influenced by the One Health approach, increasing efforts have recently been made to address this knowledge gap. Disease emergence and spread is strongly influenced by host density and contact structures, pathogen characteristics and pathogen population and molecular evolutionary dynamics in different host species, and host response to infection. All these mechanisms are strongly influenced by eco-social processes, such as globalization and urbanization, which lead to changes in global ecosystem dynamics, including patterns of mobility, human population density and contact structures, and food production and consumption. An improved understanding of epidemiological and eco-social processes, including their interdependence, will be essential to be able to manage diseases in these circumstances. The interfaces between wild animals, domestic animals and humans need to be examined to identify the main risk pathways and put in place appropriate mitigation. Some recent examples of emerging infectious disease are described to illustrate eco-social processes that are influencing disease emergence and spread.